Annealing‐Free, High‐Performance Perovskite Solar Cells by Controlling Crystallization via Guanidinium Cation Doping. Issue 7 (4th June 2021) - Dong, Hang; Pang, Shangzheng; He, Fengqin; Yang, Haifeng; Zhu, Weidong; Chen, Dazheng; Xi, He; Zhang, Jincheng; Hao, Yue; Zhang, Chunfu
Abstract : One of the urgent key points to realize the commercialization of perovskite solar cells (PSCs) with robust and excellent performance is the fabrication of high‐quality perovskite film. Nevertheless, a traditional thermal annealing (TA) technology is always necessary for a high crystallization perovskite film, and previous reports have suggested that TA could induce heterogeneous nucleation which is inconducive for the formation of smooth and uniform perovskite film, as well as time and cost consuming. Herein, an approach for the annealing‐free high‐quality perovskite film via the introduction of guanidinium iodine (GAI) is proposed. The organic molecule guanidinium (GA + ) has a large ionic radius, and this could control the crystallizing rate of annealing‐free perovskite film. Ultimately, a perovskite film with larger grain size and lower defect density is acquired through doping 0.10 mol mL −1 GAI in the precursor solution. Moreover, the fabrication of the electron transfer layer and hole transfer layer is further realized at room temperature. Thus, all room temperature, annealing‐free high‐performance PSCs are demonstrated. Notably, a GAI‐doped device with an outstanding power conversion efficiency (PCE) of 19.25% is obtained, much higher than 16.78% of the pristine device. Abstract : Annealing‐free perovskite solar cells with power conversion efficiency of 19.25% are fabricated by doping guanidinium iodine (GAI) in precursor solution. The results indicate that GAI could promote the formation of an intermediate phase. Moreover, the intermediate phase with GAI also becomes more stable, for which its transformation into perovskite crystal becomes relatively slow, the perovskite film quality is also improved.